1999
DOI: 10.1152/ajpgi.1999.276.2.g387
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of atropine-induced postprandial dysrhythmias with gastric pacing

Abstract: Gastric pacing has received increasing attention recently. However, few studies have systematically assessed the effect of pacing on gastric dysrhythmias. The aims of this study were to investigate the effect of gastric pacing on gastric dysrhythmia and to explore whether the effect of gastric pacing was mediated via cholinergic nerves. Eight hound dogs implanted with three pairs of serosal electrodes were studied. Three study sessions were performed on each dog. The experiment was conducted sequentially as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 31 publications
4
64
0
Order By: Relevance
“…Entrainment of gastric slow waves or pacing has been reported in a number of studies with GES of long pulses with a pulse width in the order of a few hundred milliseconds. 26,[28][29][30][31][32] Typically, GES was performed at a frequency slightly higher than the measured intrinsic frequency of gastric slow waves. When entrainment or pacing occurs, the natural slow waves are phase-locked with stimuli.…”
Section: Alterations Of Gastric Slow Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrainment of gastric slow waves or pacing has been reported in a number of studies with GES of long pulses with a pulse width in the order of a few hundred milliseconds. 26,[28][29][30][31][32] Typically, GES was performed at a frequency slightly higher than the measured intrinsic frequency of gastric slow waves. When entrainment or pacing occurs, the natural slow waves are phase-locked with stimuli.…”
Section: Alterations Of Gastric Slow Wavesmentioning
confidence: 99%
“…37,38 While the exact mechanisms involved in the normalization of gastric dysrhythmia with long pulse/low frequency GES are unclear, it is known that it does not involve the vagal or cholinergic pathway. 32,36 A recent study reported the entrainment of slow waves in the absence of interstitial cells of Cajal (ICC) in mice, suggesting that pacing can be achieved without ICC. 39 Similar findings were also reported in in vitro studies in ICC knocked out mice.…”
Section: Alterations Of Gastric Slow Wavesmentioning
confidence: 99%
“…Numerous studies have indicated that gastric dysrhythmia is detected during nausea [1][2][3][5][6][7][8]. It is not only found in several clinical circumstances, but is also induced by chemical agents such as epinephrine [21]; glucagons [22]; metenkephalin, or PGE 2 [23]; atropine sulfate; neostigmine [11,24,25]; morphine; histamine [25]; insulin; secretin; CCK-pancreozymin; pentagastrin [26]; and serotonin (5-HT 3 ) [27]. However, nausea is not necessarily caused by administering these chemical agents.…”
Section: Discussionmentioning
confidence: 99%
“…GES has been investigated as a therapeutic option in the management of refractory gastroparesis (1,12,15,18,20) and morbid obesity (6 -8). A number of reports is available in the literature on GES with long pulses, demonstrating beneficial effects of this approach on gastric motor and sensory functions (3,9,16,18,20,22,28). However, little is known on the effects of GES on other organs of the gut.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of stimulation pulse width, GES can be classified into three categories: long pulses (on the order of milliseconds), short pulses (in the order of microseconds), and pulse trains. Although some of the results are still controversial, the majority of these studies seems to indicate that GES with long pulses at a low frequency (close to or slightly higher than intrinsic gastric slow-wave frequency) is able to normalize gastric dysrhythmias, entrain gastric slow waves, and accelerate gastric emptying (3,10,16,18,20,22). GES with short pulses at a high frequency (4 times or much higher than intrinsic gastric slow waves) is able to significantly reduce symptoms of nausea and vomiting but is minimally effective on gastric motility (1,5,9,11,12).…”
mentioning
confidence: 99%